Pengaruh Faktor Finansial Dan Faktor Non Finansial Terhadap Kinerja Keuangan Pemerintah Desa - Elmiza Elmiza; Fefri Indra Arza (Universitas Negeri Padang, 2020)
This study aims to determine the effect of Financial Factors (Original Village Income, Transfer Funds, Other Income, Village Expenditures and Extra Time Budget Calculation / SiLPA) and Non-Financial Factors (Area of Village Area, Number of Population, Size of Village Government, Educational Background of Village Head, and Term of Office village head) on the Financial Performance of the Village Government in the nagari in Tanah Datar District in 2016-2018. The data use secondary data. The sampling technique uses Simple Random Sampling method with a total sample of 47 villages with a period of time of 3 years. Analysis of the data using multiple linear regression analysis.The results showed that Original Village Income, Transfer Funds, and Size of Village Government had a negative and significant effect on the Financial Performance of the Village Government. Village Expenditures Government had a positive and significant effect on the Financial Performance of the Village Government. Other Income, Extra Time Budget Calculation/SiLPA, Area of Village Area, Number of Population, Educational Background of Village Head, and Term of Office village head had no effect onthe Financial Performance of the Village Government.